Analysis of the influence of size, capital adequacy ratio, loan to deposit ratio, non performing loan on the profitability of commercial Banks Registered at OJK - Finoliya Wahyu Gita Rosa; Nur Suci Mei Murni (Institute of Computer Science (IOCS), 2023)
This study aims to analyze the effect of SIZE, Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non-Performing Loans (NPL) on the profitability of national private commercial banks proxied by Return on Assets (ROA). The population in this study are foreign exchange national private commercial banks registered with the Financial Services Authority (OJK) for the 2018-2021 period. Sampling used a purposive sampling method with the criteria of national foreign exchange private commercial banks registered with OJK during the 2018-2021 period, national foreign private private public banks that have issued financial reports as of December 31 during the 2018-2021 period, as well as national foreign exchange private commercial banks that has complete data and information needed in research during the 2018-2021 period. The number of samples used in this study were 40 foreign exchange national private commercial banks. This study uses data obtained from the Bank's Annual Financial Report issued by each bank. The analysis technique used is multiple linear regression analysis and using a quantitative approach.From the simultaneous hypothesis test results (F test) it shows that SIZE, Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non-Performing Loans (NPL) together have an effect on Return on Assets (ROA) with a significant value 0.000. Partially (t test) shows that SIZE, Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) have no effect on Return on Assets (ROA), while Non Performing Loans (NPL) have an influence on Return on Assets (ROA).